Elderly perception of hypertension and its treatment in Gianyar District, Bali - Ida Ayu Ratna Trisna; Duarsa, Dyah Pradnyaparamita; Ani, Luh Seri (Universitas Udayana, 2024)
Background and purpose: The risk of hypertension increases in the elderly, while treatment adherence plays a crucial role in controlling blood pressure in the elderly. This study aims to explore the elderly's perception of hypertension and its treatment. Methods: This study used an exploratory qualitative design. Data were obtained through in-depth interviews about the elderly's perception of hypertension and its medication, health-seeking behavior, and cues to action in undergoing treatment for 6 elderlies with hypertension and 4 health workers in Gianyar District in July-September 2020. The data obtained were analyzed using thematic methods. Results: This study identified 2 big themes, namely the elderly's perception of hypertension and seeking behavior. The elderly's perception of hypertension is described from the perceived vulnerability from the aspect of age, lifestyle, and heredity. Hypertension is seen as a serious disease by the elderly, particularly from the complications aspect, while complaints felt are not considered serious unless they interfere with activities or have to undergo treatment. Reduced complaints and controlled blood pressure are the perceived benefits of treatment and lifestyle adjustments: long-term medication, side effects of drugs, and traditional medicine as obstacles for the elderly in undergoing treatment. The elderly seek treatment based on their trust and comfort in health workers, infrastructure, access to health services, and support from health workers and the government. Conclusion: The perception of barriers to treatment and health-seeking behavior of the elderly in seeking treatment play a significant role in determining the medicational therapy that the elderly undergoes, which can prevent complications. Family support for the elderly is essential in overcoming obstacles and increasing elderly adherence to medication.